2007
DOI: 10.1016/j.neulet.2006.12.054
|View full text |Cite
|
Sign up to set email alerts
|

The 5-HT7 receptor influences stereotypic behavior in a model of obsessive-compulsive disorder

Abstract: The 5-HT 7 receptor has been suggested as a new putative target for the treatment of neuropsychiatric disorders, especially depression. This hypothesis is based on the finding that antidepressant drugs have relatively high affinity for the 5-HT 7 receptor, and that inactivation or blockade of the receptor leads to an antidepressant-like profile in behavioral models and sleep parameters. Obsessivecompulsive disorder is also believed to involve the serotonergic system and is treated using antidepressants, thus i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 36 publications
2
55
0
1
Order By: Relevance
“…Finally, antagonism of 5-HT7-R, via systemic SB-258719 or SB-269970 treatment, also produces antidepressant-like effects, and there is preliminary evidence that this receptor is upregulated by stress (Guscott et al, 2005;Hedlund et al, 2005;Wesolowska et al, 2006;Yau et al, 2001). Along similar lines, Htr7 knockout gene knockout produces an antidepressant-like (and in some studies anxiolytic-like) phenotype and decreased paradoxical sleep (Guscott et al, 2005;Hedlund et al, 2005;Hedlund and Sutcliffe, 2007).…”
Section: -Ht4 5-ht5a 5-ht6 and 5-ht7 Receptorsmentioning
confidence: 95%
“…Finally, antagonism of 5-HT7-R, via systemic SB-258719 or SB-269970 treatment, also produces antidepressant-like effects, and there is preliminary evidence that this receptor is upregulated by stress (Guscott et al, 2005;Hedlund et al, 2005;Wesolowska et al, 2006;Yau et al, 2001). Along similar lines, Htr7 knockout gene knockout produces an antidepressant-like (and in some studies anxiolytic-like) phenotype and decreased paradoxical sleep (Guscott et al, 2005;Hedlund et al, 2005;Hedlund and Sutcliffe, 2007).…”
Section: -Ht4 5-ht5a 5-ht6 and 5-ht7 Receptorsmentioning
confidence: 95%
“…Mice lacking the 5-HT 7 receptor were further found to be more prone to induced seizures, suggesting the receptor's implication in epilepsy (Bourson et al 1997;Witkin et al 2007). Clinical studies have suggested 5-HT 7 receptor's antagonists to act as a treatment option in depression and mood disorders (Mnie-Filali et al 2011), OCD (Hedlund and Sutcliffe 2007) as well as anxiety disorders (Wesolowska et al 2006). The receptor has also been linked to migraine (Wang et al 2010b), pain (Leopoldo et al 2011) and irritable bowel syndrome (Zou et al 2007).…”
Section: -Htmentioning
confidence: 99%
“…This disorder has been proven very difficult to model in laboratory animals, which is demonstrated by the large number of models tried out [66]. Marble burying is one of the more well-established models for OCD; however, as anxiolytic agents, such as diazepam and buspirone, have been shown to reduce burying behavior, some investigators consider this more as a model for anxiety [131,132].…”
Section: Obsessive-compulsive Disordermentioning
confidence: 99%
“…2 Hypothetical model of the induction of hypothermia by an antagonistic 5-HT7R/5-HT1AR-heterodimer. 5-HT-induced hypothermia is mediated by the 5-HT7 receptor at low 5-HT levels, while higher levels of 5-HT also activate the 5-HT1A receptor, which also induces hypothermia and allosterically inhibits 5-HT7 receptor activity burying [66]. Thus, antagonism at the 5-HT7 receptor might also be a valuable approach for the treatment of OCD.…”
Section: Obsessive-compulsive Disordermentioning
confidence: 99%